Hot herbal compresses as therapy for reducing labor pain levels in the first stage of active phase in primigravida - Sofika Larasati; Noor Pramono; Djamaluddin Ramlan (Universitas Airlangga, 2022)
HIGHLIGHTS 1. Labor pain, a physiological during labor, is regared as the most severe pain experienced by women.2. Hot herbal compress was provided as a therapy for reducing labor pain level in the first stage of active phase in primigravida.3. Hot herbal compress was found to have an effect as a therapy for reducing labor pain level in the first stage of the active phase of primigravida. ABSTRACT Objective: To prove the effect of providing hot herbal compresses as a therapy for reducing the level of labor pain in the first stage of the active phase of primigravida Materials and Methods: This was a true experimental study using pretest and posttest designs with control group. There was an intervention group (n=19) which was provided with hot herbal compress therapy for 20 minutes with a temperature between 37-51.5oC and a control group (n=19) receiving breathing exercise therapy. Respondents were selected by inclusion and exclusion criteria and randomization was carried out to determine whether the respondents were included in the intervention or control group by drawing lots. Results: Hot herbal compress therapy reduced the level of labor pain in the first active phase at the 1st hour treatment by 49.3% (p=0.000), the 2nd hour by 50.3% (p=0.000), and the third hour by 22.4% (p=0.009). Conclusion: Hot herbal compresses have an effect as a therapy for reducing pain levels of labor in the first stage of the active phase of primigravida.